Short-term effects of air temperature on blood markers of coagulation and inflammation in potentially susceptible individuals. Issue 9 (25th July 2012) - Schäuble, Claudia Luise; Hampel, Regina; Breitner, Susanne; Rückerl, Regina; Phipps, Richard; Diaz-Sanchez, David; Devlin, Robert B; Carter, Jacqueline D; Soukup, Joleen; Silbajoris, Robert; Dailey, Lisa; Koenig, Wolfgang; et al.
Abstract : Objectives: Changes in air temperature are associated with an increase in cardiovascular events, but the role of procoagulant and proinflammatory blood markers is still poorly understood. The authors investigated the association between air temperature and fibrinogen, plasminogen activator inhibitor type 1, interleukin-6 and high-sensitivity C reactive protein in two potentially susceptible groups. Methods: This prospective panel study was conducted between March 2007 and December 2008 in Augsburg, Germany. The study population comprised 187 participants with type 2 diabetes mellitus or impaired glucose tolerance and 87 participants with genetic polymorphisms on the detoxification and inflammation pathways. Overall, 1766 repeated blood measurements were collected. Hourly meteorology data were available from a central measurement site. The association between temperature and blood markers was analysed with additive mixed models. Results: For type 2 diabetes mellitus and impaired glucose tolerance participants, the authors observed immediate, lagged and cumulative increases in fibrinogen (range of percentage changes in geometric mean: 0.6%–0.8%) and plasminogen activator inhibitor type 1 (6.0%–10.1%) in association with a 5°C temperature decrement. Participants with a body mass index above 30 kg/m 2 as well as females showed particularly strong fibrinogen effects. In participants with the special genetic background, 5°C decreases in the 5-day average of temperature led to a change of 8.0% (95% CI 0.5% to 16.2%) in interleukin-6 and of −8.4% (95% CI −15.8% to −0.3%) in high-sensitivity C reactive protein, the latter driven by physically active individuals. Conclusions: The authors observed different temperature effects on blood markers in two potentially susceptible groups probably indicating varying underlying biological mechanisms. This study results might provide a link between temperature and cardiovascular events.